LOCAL GOVERNMENT CONFLICTS AND PUBLIC SERVICE EROSION: A CRITICAL POLITICAL ETHICS ANALYSIS - Dwi Astutik; Muhammad Falah Alfitamma (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyse conflicts in local leadership from the perspective of political ethics theory, examine their impact on the quality of public services, and formulate strategies for strengthening political ethics in local government governance. The study employs a qualitative approach using the library research method. Data were obtained from various academic literature, nationally and internationally reputable journals, policy documents, and regulations relevant to political ethics, public leadership, and public services. The findings indicate that local leadership conflicts have the potential to erode public services through weakened governmental coordination, increased politicisation of the bureaucracy, hindered policy implementation, and a decline in public trust in local government. This study also found that the application of political ethics principles, such as integrity, accountability, public responsibility, and ethical leadership, is a key factor in maintaining the effectiveness of public services and the quality of governance. Therefore, strengthening political ethics is necessary to create a local government that is professional, responsive, and oriented towards the interests of the community